Prevalence of trematodes of the Paramphistomatidae family in cattle of Yurimaguas district, province of Alto Amazonas, Loreto - Pinedo V., Rosa (2010)
The prevalence of Paramphistomids in cattle of Yurimaguas district, Alto Amazonas province, Loreto was evaluated. Fecal samples from 421 cattle were collected since June 2006 till February 2007 for the coproparasitological evaluation using the spontaneous sedimentation technique. The resulting prevalence was 44.2 ± 4.7%. The logistic regression test indicated that age (p<0.05), and not sex was a risk factor where animals over three years of age had three times more risk to suffer the disease than younger animals. The high prevalence of Paramphistomosis observed in the cattle population might be influenced by favorable environmental conditions in the study area, as well as the lack of prevention and control strategies in the local cattle population.